Formulation of anti-acne gel containing Citrus aurantifolia (Christm.) and Aloe barbadensis (L.) extracts and evaluating the impact of high-pressure and microwave processing - Kuai, Fiong Hin; Kaiser Mahmood,; Nor Amaiza Mohd Amin,; Norazlinaliza Salim,; Yus Aniza Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Acne is one of the most prevailing skin disorders caused by bacteria, dead skin cells, and oil clogging of hair follicles. In this study, a polyherbal anti-acne gel containing C. aurantifolia and A. barbadensis extracts was developed as a cosmeceutical. Major bioactive fractions in the plant extracts were evaluated by gas chromatography-mass spectrometry (GCMS) analysis. Moreover, C. aurantifolia depicted higher total phenolic, flavonoids, tannins, and ascorbic acid than A. barbadensis extract. The anti-acne gel was prepared by adding 1% of both plant extracts and evaluated for organoleptic properties (color, odor, homogeneity, consistency, washability), spreadability, viscosity, extrudability, pH, and drug contents and compared with a commercial herbal formulation (NuTeen®). The developed gels depicted greater inhibition of Staphylococcus aureus than the commercial formulation with a growth inhibition diameter of 2.40 mm. In-vitro permeation of plant extracts from a gel into phosphate buffer was found at 27.4% after 2.5 hr, and the release behavior was best explained by the Higuchi model (R2=0.97). Finally, for the possible replacement of paraben (synthetic preservative) from the gel, high-pressure processing (600 MPa, 120 s), and microwave pasteurization (700 W, 80 s) were adopted and the stability of gels was evaluated after 4 weeks, and found comparable to their paraben-containing normal counterpart.